Performing representation: Women members in the Indian parliament - Rai, Shirin M.; Spary, Carole (New Delhi Oxford, 2019)
This book offers new insights into the gendered nature of the performance, aesthetics and norms of parliamentary life through an examination of electoral data, legislative debates and life stories of women MPs.